INVESTIGATION OF PARASITIC INFECTION AMEBIASIS AMONG A POPULATION IN AL-SAMAWAH CITY/ AL-MUTHANNA PROVINCE BY USING MOLECULAR METHOD REAL-TIME POLYMERASE CHAIN REACTION - Dunnia Abdullah Barakat (Al-Qadisiyah Journal of Pure Science, 2019)
Entamoeba histolytica parasite is widely distributed throughout the world, but prevalence rates are highest in developing countries . E.histolytica infection ,Amebiasis, is consistently present among the poor developing countries, this study aim to investigate the amoeba parasites in the city of Al-Muthanna province using microscopic and molecular methods to explain the spread of the disease in this city because of its importance to the health of individuals in society where we use microscopic examination and PCR technology to investigate the amoeba parasites and found the percentage of amoeba parasites was 69.2307690 % and the negative samples were 30.769231% from the 286 total sample, a significant difference below the significant level pâ‰¤00.05 in the incidence of parasitic infection.